Transformation of BOS Fund Management: Synergy Between Education Reports and School Accountability - Safarudin; Muhammad Syaifuddin; Nunu Mahnun (Institut Agama Islam An-Nawawi Purworejo, 2025)
The urgency of transparency and accountability in the management of School Operational Assistance Funds (BOS) has increased in line with public demands for clean and effective education governance, especially in island regions with limited facilities, human resources, and access to technology. This study aims to examine strategies for implementing transparency and accountability in the management of BOS based on Education Reports in schools in island regions. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation, then analyzed using triangulation techniques to ensure the validity of the findings. The results show that transparency is realized through open budget information, RKAS socialization, and periodic reporting, while accountability is reflected in transaction recording, internal verification, external audits, and the use of the ARKAS application. The main obstacles include low human resource capacity, minimal digital infrastructure, and a lack of understanding of the Education Report Card system. Strategic efforts were made through internal training, collaboration with the community, and budget priorities for improving literacy, numeracy, and teacher professional development. In conclusion, the integration of BOS and the Education Report Card contributed to improving the effectiveness of fund use, learning quality, and public trust, making it a suitable model for education fund management in 3T areas.